Acknowledgment, Harming, and Political Trauma: Reflections After the Plague Year. Issue 3 (2nd September 2021) - Benjamin, Jessica
Abstract : The author suggests that we use the lens of acknowledging harm to approach the political events of the pandemic, the revelation of the depth of racial inequity and injustice, as well as the neoliberal capitalism that holds oppression in place, contributing to the emiseration of the precariat. Beginning with the idea of knowing terrible things, she considers the inability of members of the liberal elite to actually name, know and confront the harm being done. The contradictory position of implicated subjects benefiting from systems of domination while nominally opposing their injustice is considered in light of the dissociative effort to protect the sense of goodness despite knowing otherwise. This self-protection is related to the imaginary construct Only One Can Live which the author elaborates as an aspect of the position of "doer and done to." By contrast to that complementary opposition, she suggests the position of the moral Third in which we can acknowledge and repair harm; we can truly know what has been done wrong and take responsibility for putting it right. As opposed to clinging to the sense of goodness, the collective efforts on behalf of repairing harm allow us to contain knowing and bear the sense of badness; as co-created action they embody an intersubjective relation to the moral Third.